Analytical and numerical analyses on stiffness enhancement of ground improved by head-enlarged CDM columns - Hoàng, Duy Phương (2020)
Point Foundation (PF) method is an advanced technology introduced by EXT Co. Ltd company from Korea, which has more advantages than CDM method. The shape of PF columns makes a big difference in settlement compared to conventional CDM. This study presents a comparative study on stiffness enhancement of grounds improved by Point Foundation method and by the conventional CDM method using analytical and numerical analyses. In addition, the analysis results are compared with experimental program